AKUNTANSI PERNIKAHAN DI PULAU LOMBOK: Ali Fikri, Nina Karina Karim, Widyastuti - Fikri, Muhammad Ali; Karim, Nina Karina; Widyastuti, W (Jurnal Riset Akuntansi Aksioma, 2017)
The objective of this study is to analyze marriage from the accounting perspective. This study examined whether a husband (wife) was recognized as revenues, expenses, assets, or liabilities. Using a sample of 20 people as respondents on Lombok island community who have experienced divorces, the study conclude that marriage is regarded as expense and liabilities, instead of income or assets.Keywords: marriage, assets, revenues, expenses, liabilities